Image Classification of Wayang Using Transfer Learning and Fine-Tuning of CNN Models - Banjaransari, Muhammad; Prahara, Adhi (Universitas Ahmad Dahlan, 2023)
Wayang (shadow puppetry) is a traditional puppetry used in a performance to tell a story about the heroism of its main characters. Wayang has gained recognition as a cultural masterpiece by UNESCO. However, this cultural heritage now declining and not many people know about wayang. One of the solutions is using computer vision technology to classify wayang images. In this research, a transfer learning approach using Convolutional Neural Network (CNN) models namely MobileNetV2 and VGG16 followed by fine-tuning was proposed to classify wayang. The dataset consists of 3,000 images divided into 30 classes. This data is split into training and test data that are utilized for training and evaluating the model. Based on the evaluation, the MobileNetV2 model achieved precision, recall, F1-score, and accuracy of 95%, 94%, 94%, and 94.17%, respectively. Meanwhile, the VGG-16 model obtained 93% for all metrics. It can be concluded that transfer learning and fine-tuning using the MobileNetV2 model produces the best result in classifying wayang images compared to the VGG16 model. With good performance, the proposed method can be implemented on mobile applications to provide information about wayang from the captured images, thus indirectly supporting the preservation of cultural heritage in Indonesia.